POLA INTERAKSI KOMUNIKASI PIMPINAN TERHADAP KRU TVPEDULI DALAM MENCIPTAKAN KENYAMANAN KERJA - akbar, Muh.Akbar; Saleh, Muhammad; Zulfah (Communication and Islamic Broadcasting Studies IAIN Parepare, 2025)
Muh. Akbar, Communication Pattern of Leaders Towards tvPeduli Crew in Creating Work Comfort (Mr. Dr. Muhammad Saleh, M.Ag as the Main Supervisor and Mrs. Dr. Zulfa, M.Pd. as the Assistant Supervisor) TV Peduli is a local TV that is used as an information media and a forum for public participation, by presenting healthy, intelligent, and quality information and inspiration as well as a variety of local and national content. And where the human resources that must operate must be qualified so that they can provide shows like national TV and private TV. This research is a qualitative research that uses the Leaders and crew of TV Peduli as research sources and focuses on. Communication patterns of leaders towards TV Peduli crew in creating work comfort. The results of this study are communication patterns that refer to total channel patterns. This means a communication flow that ensures all group members can directly communicate with other members without intermediaries. Communication science views patterns: as communication flows that have several models and are influenced by several factors that are formed, one of which is from organizational policies and leadership models. The participatory leadership model provides a great opportunity for the formation of a total channel communication pattern. With this pattern, coordination is one of the things that becomes an added value so that in its implementation it can increase work comfort in an institution, including in the TV Peduli environment.